(3GdfSHI Edi GdehGVY hGdHdOGfs - (3YHO Gddg Hf YHO Gddg Hf CMeO eNQeI, CHh eMeO , GdWjH HGeNQeI,J (B947 (3g` s ((3Ydi Hf Ydi Hf CMeO Hf Ydi GdjeGfi s)
(3ChdgG (B:s
(3GdMeO ddg MeOkG jhGai fYeg hHYO , aEf cJGHi gPG LeYJg dfaSi hdef jfJaY Hg ef HYOi hSHH LeYi dg Cfi hbaJ Ydi cJGH ai GdCfSGH Edi GdbHGFd hGdBHGA s
(3BNQgG (B:s
(3hCeG CHh GdegGLQ OjfGQ Hf YHO Gddg GdfghPi fhf hPGd eYLeI CMO CeQGA GdeZQH deYGhjI bHd SfI KdGKI hSJjf ef GdgLQI Je MQa GdjGA hHJeGeg Je GdcJGH HYhf Gddg s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde Hg VHWs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B45s
Keywords: (3GdJGQjNs